Distinct astrocyte activation patterns associated with neuroinflammation induced by gamma and proton beam irradiation - Liben Yan; Tianyi Er; Shaoqian Sun; Yulin Deng; Zhirong Wan; Jing Zhao; Ailu Wang; Beiqin Liu; Qiaojuan Wang; Li Sui; Hong Ma (Scientific Reports)
Abstract The aim of this study was to investigate the impact of radiation exposure on astrocyte response and assess their potential roles and mechanisms in surrounding neural cells. Healthy male rats were irradiated different radiation types to induce the neural inflammation. U87-MG cells were exposed respectively to gamma rays (2 Gy and 10 Gy) and proton irradiation (0.1 Gy and 0.5 Gy). Cell viability, mRNA expression, mitochondrial membrane potential, glucose uptake and cytokine levels were analyzed respectively to evaluate the neuroinflammation or neural damage. Gamma rays and proton beam irradiation induced distinct patterns of inflammatory factor expression in the hippocampal region of rats. Moreover, we observed changes in cell morphology and a dose-dependent inhibition of cell proliferation across all radiation types. Significant upregulation of caspase-8 and caspase-3 enzymatic activities in U87-MG cells was observed after exposure to gamma rays. Astrocytes showed increased expression of GFAP, C3, and PTX3 after exposure to gamma rays, and downregulation while exposure to proton. Additionally, proton beam irradiation potentially increased glutamine synthesis in astrocytes. Furthermore, we investigated the influence of irradiated astrocytes on neurons via mitochondrial integrity, neurotransmitter levels, and glucose metabolism. Additionally, the expression of miR92a-3p, which can significantly downregulate GFAP and IL-6 expression, was downregulated by gamma rays, while upregulated by proton irradiation. The findings highlight the differential impact of gamma rays and proton radiation on inflammatory responses in vivo, with gamma rays inducing a pro-inflammatory effect and proton radiation exerting anti-inflammatory properties. Overall, this study provides valuable insights for radiotherapy management.